2011
DOI: 10.5539/ies.v4n2p198
|View full text |Cite
|
Sign up to set email alerts
|

Students' Entrepreneurial Inclination at a Malaysian Polytechnic: A Preliminary Investigation

Abstract: This paper reports preliminary results of an ongoing project to examine students' inclination towards entrepreneurship at a Malaysian polytechnic. The study used a self-administered questionnaire to explore the influence of entrepreneurial intent, perceived behavioral control, self-efficacy, perceived barriers, perceived support factors and attitude towards entrepreneurship in technical and non-technical student samples. Findings of this study revealed that non-technical students were more inclined to become e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The article is in line with other research that is based on surveys of university students (Fatoki, 2014;Udofia & Essien, 2013;Yasin, Mahmood, & Jaafar, 2011;Zellweger, Sieger, & Halter, 2011;Zhao, Seibert, & Hills, 2005), but gives greater emphasis to how expectations and aspirations about the labor market are related to aspirations and expectations in the family field.…”
Section: Introductionsupporting
confidence: 83%
“…The article is in line with other research that is based on surveys of university students (Fatoki, 2014;Udofia & Essien, 2013;Yasin, Mahmood, & Jaafar, 2011;Zellweger, Sieger, & Halter, 2011;Zhao, Seibert, & Hills, 2005), but gives greater emphasis to how expectations and aspirations about the labor market are related to aspirations and expectations in the family field.…”
Section: Introductionsupporting
confidence: 83%
“…In contrast, one study indicated that Nigerian students from rural areas had a more favorable attitude toward technical education than metropolitan areas (Lawal, 2012). People with a business background exhibited more favorable opinions about entrepreneurship than those with an engineering background (Yasin et al, 2011) Based on the PPPM (PT) policy to solve the problem of lack of student enrolment to TVET, among the problems presented are unclear paths and articulation of TVET route, the perception that TVET is a second-class education and TVET administrative structure in the country seen unstructured as different ministries are implementing TVET Education. The challenges presented in this article with the addition of factors influencing the student enrolment created a negative discernment among the general public.…”
Section: Discussionmentioning
confidence: 91%
“…According to one research, arts and vocational design course constitute a costly curriculum for the administration (Indoshi et al, 2010). According to research by Yasin et al (2011), a more significant percentage of Malaysian technical students said it was difficult to obtain financial aid to start a firm. Friends, relatives, classmates, and educators all have a part in shaping people's interests and persuading them to start their businesses (Zain, et al, 2010;Abdullah & Sulaiman, 2013;Ibrahim & Bakar, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are many other factors that influence students about choosing entrepreneurship as a career path after graduation. One of the factors is educational background [56]. It shows that students in non-technical fields who have any involvement with entrepreneurship education have a higher tendency to become entrepreneurs within a short period of time after graduation compared to students in more technical fields who have also participated in entrepreneurship education programs.…”
Section: Discussionmentioning
confidence: 99%